Implementasi Pendekatan Kognitif Dalam Pembelajaran IPAS di SDN 01 Demangan - Salsabila Qurotu Aini, (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
This research examines the implementation of a cognitive approach in science and science learning at SDN 01 Demangan. This research aims to increase students' knowledge about the importance of science education. Apart from that, this research also aims to shape the character of love for nature and social for students through a cognitive approach because today's children really lack an understanding of love for nature and social. The results of the research show that understanding the implementation of the cognitive approach is effective enough to be provided during science learning. The cognitive approach emphasizes that behavior is a mental process in which individuals (organisms) are active in capturing, assessing, comparing, and responding to stimuli before reacting. Individuals receive a stimulus and then carry out mental processes before reacting to the stimulus that comes.